Benin : 2012 Article IV Consultation and Fourth Review Under the Extended Credit Facility Arrangement-Staff Report; Staff Supplements; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Benin. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
Benin has made significant progress in consolidating macroeconomic stability under the IMF-supported program. Its prudent fiscal policy has kept fiscal deficits at manageable levels and is projected to yield a basic primary surplus in 2012. The Executive Board of the International Monetary Fund (IMF) suggested that the authorities hold current expenditures to provide space for infrastructure spending and meet medium-term fiscal objectives. Benin's authorities are committed to maintain sound macroeconomic policies, pursue the implementation of critical structural reforms, and take further measure to achieve program objectives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet